DIAGNOSTICS OF ROTOVIRUSES BY ELISA IF IN ACUTE INTESTINAL INFECTIONS - Yodgorova, N.T.; Khalilov, Z.S.; Sharapov, S.M. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Rotavirus improves the biological method of the immunoenzyme, which causes acute intestinal diseases. Materials and methods: 665 patients with diarrhea were admitted to the department of intestinal diseases of the 4th Children’s Infectious Diseases Hospital in Tashkent and 151 patients with diarrhea in the Bukhara Regional Infectious Diseases Hospital. Results: This article is devoted to the method of detection and diagnosis of rotoviruses from the patient’s stool using ELISA, which is used for the first time in Uzbekistan. Of 816 cases of acute intestinal infections in Tashkent and the Bukhara region, 51 children (6.25%) were diagnosed with rotavirus infection. The sensitivity of this method was 98.7%, and the specificity was 98.4%. Conclusion: IFA-screening of rotavirus in feces is a cost-effective method that allows fecal examination of 92 patients at the same time (2–2.5 hours).